2009
DOI: 10.1007/s00442-009-1444-4
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific nest-site preference and success in eiders

Abstract: Variation in nest concealment is puzzling given the expected strong selection for safe nest sites. Selecting a concealed nest may decrease the risk of clutch predation but hinder parents from escaping predators, providing a possible solution to this paradox. Because the relative value of current versus future reproduction may vary with breeder age or state, nest concealment may also vary as a function of these attributes. We tested four predictions of the female and clutch safety trade-off hypothesis in eiders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 53 publications
4
76
0
Order By: Relevance
“…Other diVerences in females with few developing follicles might also be expected, such as later laying start or smaller eggs, for which there was likewise no evidence. Still another possibility is that females which persisted laying after early egg predation were older and more experienced birds, with larger clutches (Öst and Stele 2010). However, experienced females also tend to lay earlier than others (Baillie and Milne 1982), but there was little diVerence in laying date between abandoned and other nests, casting doubt on this explanation.…”
Section: Discussionmentioning
confidence: 94%
“…Other diVerences in females with few developing follicles might also be expected, such as later laying start or smaller eggs, for which there was likewise no evidence. Still another possibility is that females which persisted laying after early egg predation were older and more experienced birds, with larger clutches (Öst and Stele 2010). However, experienced females also tend to lay earlier than others (Baillie and Milne 1982), but there was little diVerence in laying date between abandoned and other nests, casting doubt on this explanation.…”
Section: Discussionmentioning
confidence: 94%
“…We hypothesize that first nest date represents only a handful of the fittest or most determined individuals, whereas the 50 % threshold at least awaits the arrival of half the population and may better represent the general public. An alternative hypothesis is to view common eiders as pioneers and followers, where such grouping of each individual could be determined by personality (Seltmann et al 2014), body condition (Parker and Holm 1990;Ö st and Steele 2010), affinity for public information (Valone 2007) or an interaction of these factors (Seltmann et al 2012). Our study colony of common eiders is somewhat unique in being densely occupied by nesters and also having high incidence of nest parasitism but probably is representative for other such colonies and also valuable in providing insights into a population that is healthy and stable, with high adult survival (Jónsson and Lúðvíksson 2013).…”
Section: Resultsmentioning
confidence: 99%
“…At least three individual traits can drive individual females to arrive early and try to obtain a favored nest site. One obvious candidate is body condition and its relationship with stress or nest initation date (Ö st and Steele 2010;Seltmann et al 2012) especially because body condition of individual eiders can vary from year to year (Ö st et al 2007). The choice or ability to compete for best nest sites each year could thus be positively related to body condition.…”
Section: Which Individuals Are the First Nesters?mentioning
confidence: 99%
See 1 more Smart Citation
“…Forero et al 1999;Newton 2001;Serrano et al 2001). However, as young breeders often have poor breeding success (Blums et al 1997;Devries et al 2008;Ö st and Steele 2010), this fact alone could make them more prone to disperse. The few studies that have aimed at separating the effects of nest failure and parental experience on breeding dispersal have shown that the effect of one factor can overcome the effect of another (e.g.…”
Section: Introductionmentioning
confidence: 97%